Zirconium Silicate/IL/Mxene-based composite membranes for high-temperature fuel cell applications - Edwin, Reeves Nayagam (2024)
A Master of Science thesis in Chemical Engineering by Reeves Nayagam Edwin entitled, “Zirconium Silicate/IL/Mxene-based composite membranes for high-temperature fuel cell applications”, submitted in June 2024. Thesis advisor is Dr. Amani Al-Othman. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).